Application of Video Games as Part of Learning Islamic History - Arditya Prayogi (EDUTREND: Journal of Emerging Issues and Trends in Education, 2024)
Teaching Islamic history is generally considered boring because most of the learning methods focus on storytelling. For this reason, other creative efforts are needed to make learning history enjoyable. One way is to apply video games in learning Islamic history. This is especially considering that video games apparently have a participatory dimension in learning Islamic history. This article then aims to present how video games are applied in learning Islamic history, especially conceptually considering that not many practices have been carried out systematically. This article was prepared using a qualitative approach supported by data collection methods in the form of literature studies. From the results of this study, it was found that video games can be applied in learning Islamic history if seen from their role as a medium for transferring information and values. Substantially, the form of application can be by choosing a video game as well as the game's tools and themes and then involving a mentor who directs and accompanies students to learn Islamic history well.